A lymph node mediastinal foreign body reaction mimicking nodal metastasis: A case series - Zuccatosta, Lina; Latini, Maria Agnese; Mei, Federico; Bonifazi, Martina; Barisione, Emanuela; Salio, Mario; Gasparini, Stefano; Gonnelli, Francesca (Frontiers in Medicine, 2022)
Introduction: In the last decades, many haemostatic substances included oxidized cellulose topically applied have been used during surgery and their use have become a common practice. Oxidized cellulose (OC) is one of the most used haemostatic substances. However, different studies have shown the persistence of OC deposits after surgical procedures that may simulate recurrent malignancies and abscesses. We present a case series of patients with enlarged on CT and PET-FDG positive lymphadenopathies due to foreign body inflammatory reaction to OC after lung surgery for pulmonary malignancies. Methods: Retrospective chart review of patients from 2021 to 2022 who underwent EBUS-TBNA for the characterisation of hilar and/or mediastinal lymphadenopathies and a histopathological diagnosis of foreign body inflammatory reaction to OC. Results: Eight patients were referred to “Ospedali Riuniti di Ancona” (n=7) and “Ospedale San Martino” (Genoa) (n=1) Interventional Pulmonology Units for the characterisation of hilar and/or mediastinal lymphadenopathies. All the evaluated patients underwent surgical procedures for lung cancers within the previous twelve months. EBUS-TBNA was performed in all the patients to rule out nodal metastasis. The cyto-pathological evaluation revealed amorphous acellular eosinofilic material surrounded by inflammatory reaction. As no other apparent causes might explain this finding and considering the temporal relationship between the lymphadenopathy and the lung surgery, foreign body inflammatory reaction to OC is the most likely cause of the phenomenon. Conclusion: In patients who underwent surgery for lung cancer, especially within few months, the development of lymph node foreign body reaction due to surgical material retention should always be considered.